A study of quality of life of head and neck cancer patients attending ear, nose, throat out-patient department of tertiary care centre in upper Assam region - Mili, M. K.; Sarmah, Monikuntal; Goswami, Suhanee; Saikia, Asha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Head and neck cancer makes up 3-4% of cancers, however, in developing nations like India, it constitutes 30-40% of cancer cases, primarily attributed to use of tobacco, alcohol. Methods: A hospital-based, descriptive, cross-sectional study was done in a tertiary care centre upon 54 patients during a period of 1 year. Patients were subjected to a questionnaire on quality of life, using University of Washington quality of life questionnaire (UW-QOL). Results: Out of 54 patients, 43 were males, 11 were females. Maximum cases were observed in the 6th decade of life. When asked to state the most important aspect of lifestyle for the patient in the past week, the highest percentage answered pain followed by appearance and chewing, swallowing and speech. Conclusions: Around two-fifths of patients experienced moderate pain needing regular non-narcotic medications and approximately one/fourths stated they felt significantly disfigured. Around 45% patients stated they can chew soft solids, while 30% stated that they can swallow certain soft solids, 28% stated that they can swallow only liquids and 15% were unable to swallow (choking). Around one-third of patients complained of difficulty in speech and around a third of all patients were depressed. Around 45% patients were dissatisfied with their sex lives. Around half of the patients complained of reduced salivation, attributed to radiation-induced xerostomia. One-third of the patients experienced shoulder stiffness and/or pain due to possible injury to spinal accessory nerve.